2017
DOI: 10.1371/journal.pone.0177657
|View full text |Cite
|
Sign up to set email alerts
|

Different microRNA profiles reveal the diverse outcomes induced by EV71 and CA16 infection in human umbilical vein endothelial cells using high-throughput sequencing

Abstract: Enterovirus 71 (EV71) and Coxsackievirus A16 (CA16) remain the predominant pathogens in hand, foot, and mouth disease (HFMD), but the factors underlying the pathogenesis of EV71 and CA16 infections have not been elucidated. Recently, the functions of microRNAs (miRNAs) in pathogen-host interactions have been highlighted. In the present study, we performed comprehensive miRNA profiling in EV71- and CA16-infected human umbilical vein endothelial cells (HUVECs) at multiple time points using high-throughput sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…In a previous study, we found that differentially expressed miRNAs are involved in the regulation of cell-cell junctions in 16HBE cells and HUVECs, but not in PBMCs [1, 16], whereas in PBMCs we found differentially expressed miRNAs associated with nervous system development and modulation of the immune response. This difference may be because 16HBE cells and HUVECs are epithelial cells and endothelial cells, respectively, and that cell-cell junctions play an important role in the barrier function of these cells.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…In a previous study, we found that differentially expressed miRNAs are involved in the regulation of cell-cell junctions in 16HBE cells and HUVECs, but not in PBMCs [1, 16], whereas in PBMCs we found differentially expressed miRNAs associated with nervous system development and modulation of the immune response. This difference may be because 16HBE cells and HUVECs are epithelial cells and endothelial cells, respectively, and that cell-cell junctions play an important role in the barrier function of these cells.…”
Section: Resultsmentioning
confidence: 65%
“…For example, Cui et al [23] revealed that some miRNAs show differential expression levels following EV71 and CA16 infection, and three key miRNAs (miR-545, miR-324–3p, and miR-143) can be used to distinguish EV71 infection from CA16 infection in patients with HFMD. Furthermore, our previous studies have also demonstrated that there is significant differential expression of known miRNAs in EV71- and CA16-infected human cells [1, 15, 16]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The human umbilical vein endothelial cells (HUVECs) group contains samples from enterovirus patients (n = 2), coxsackievirus patients (n = 2), and healthy controls (n = 2); GEO accession number: GSE94551 (see [50] for additional information on the samples).…”
Section: Sample Groupsmentioning
confidence: 99%